2010
DOI: 10.1007/s12275-010-0048-3
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation and production characteristics of epothilones in alkali-tolerant Sorangium cellulosum strain So0157-2

Abstract: 3-O-alpha-D-ribofuranosyl epothilone A (epothiloneoside A) is a major component of glycosylated epothilones in Sorangium cellulosum strain So0157-2. The production and glycosylation ratios of epothiloneoside A in both solid and liquid culture conditions with various pH values and carbon sources were studied. The results showed that glycosylation occurs whenever epothilones are produced, regardless of changes in pH values, production time curves, and different carbon sources. We suggest that glycosylation is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…2D-NMR analyses were carried out to further confirm the glucosylation position. The 1 H– 1 H COSY NMR analysis (Additional file 1: Figure S2 (B)) showed that the anomeric proton ( δ  = 4.49 ppm) was in a close relationship with δ  = 3.2 ppm, which was annotated to H-6 of epothilone by comparing our data with 1 H NMR of previously identified epothilone A and pentoside of epothilone as epothiloneoside A by Zhao et al [2010]. Different hydroxylated and epoxidated epothilone A have been produced by microbial biotransformation using Aspergillus niger (Wang et al [2009]) which were characterized by different NMR analyses.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…2D-NMR analyses were carried out to further confirm the glucosylation position. The 1 H– 1 H COSY NMR analysis (Additional file 1: Figure S2 (B)) showed that the anomeric proton ( δ  = 4.49 ppm) was in a close relationship with δ  = 3.2 ppm, which was annotated to H-6 of epothilone by comparing our data with 1 H NMR of previously identified epothilone A and pentoside of epothilone as epothiloneoside A by Zhao et al [2010]. Different hydroxylated and epoxidated epothilone A have been produced by microbial biotransformation using Aspergillus niger (Wang et al [2009]) which were characterized by different NMR analyses.…”
Section: Resultssupporting
confidence: 73%
“…Zhao and his group have successfully characterized a pentoside of epothilone A as epothiloneoside A in 2010 from Sorangium cellulosum So0157-2 (PCT/CN2008/001946) strain culture, and the glycosylated compound was detected as attachment of sugar in C-3 hydroxyl position with a molar mass of 625.29. The compound was determined to be 3- O - α -D-ribofuranosyl epothilone A (Zhao et al [2010]) beside this no other reports are available about glycosylated analogues of epothilone A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sorangium cellulosum So0157-2 strain (the deposition ID in the China Center of Typical Culture Collection (CCTCC) is CCTCC M 208078) was cultured in liquid M26 medium at 30 °C as previously described [38]. E. coli Top10 and BL21 (DE3) were used as the cloning host and the expression host, and pMD-T simple vector (Takara, Dalian, China) and pET-22b (+) (Novagen, Darmstadt, Germany) were used as the cloning vector and the expression vector, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…So0157-2 produces epothilones, cytotoxic macrolides that stabilize microtubules, mimicking the effects of paclitaxel on cancer cells21. More than 20 epothilone derivatives have been identified in So0157-2, including a novel glycosylated epothilone, epoAG22, a promising candidate for clinical application. The strain is an alkaline-adaptive epothilone producer that grows across a wide pH range (5.0–14.0).…”
mentioning
confidence: 99%